النظام القانوني للدعوى الإدارية الاستعجالية لحماية الحريات الأساسية - قديري, هشام (جامعة الوادي University of Eloued, 2018)
"عنوان المذكرة : النظام القانوني للدعوى الإدارية الاستعجالية لحماية الحريات الأساسية إشكالية المذكرة : هل تمكنا المشرع من توفير حماية خاصة ومستعجلة للحريات الأساسية من خلال قانون 08-09 ؟ المنهج المتبع: تعتمد هذه الدراسة على المنهج التحليلي وذلك بتحليل المواد المخصصة في باب الاستعجال في مادة الحريات الأساسية . والمنهج المقارن وذلك لمقارنة الأحكام المتضمنة في قانون الإجراءات المدنية والإدارية وقانون العدالة الإدارية الفرنسي والمسطرة المغربي والقانون الكويتي وقانون المرافعات المصري. أهم النتائج: 1- يعد تبني المشرع الجزائري للاستعجال الإداري في مادة الحريات مكسبا تشريعيا وقفزت نوعية كحماية إجرائية . 2- عدم تبني المشرع شرط ""ما لم يخالف النظام العام ""الوارد في المادة 171 مكرر في قانون الإجراءات المدنية السابق في النص الخاص بالاستعجال الإداري لحماية الحريات الأساسية أهم التوصيات : 1- الرجوع إلي نظام الفرد . 2- عدم الخلط بين قاضي الاستعجال وقاضي الإلغاء. 3- مواصلة الإصلاحات وفصل قانون الإجراءات المدنية عن قانون الإجراءات المدنية الإدارية. 4- إلغاء نظام وقف التنفيذ . 5- عدم الربط بين دعوى وقف التنفيذ ودعوى حماية الحريات الأساسية . ""Title of the Memorandum: The Legal System of the Urgent Administrative Case for the Protection of Fundamental Freedoms The Problem of the Memorandum: Has the legislator been able to provide special and urgent protection for fundamental freedoms through Law 08-09? Methodology: This study is based on the analytical method by analyzing the allocated materials as a matter of urgency in the basic liberties article. And the comparative approach to compare the provisions contained in the Code of Civil and Administrative Procedures, the French Administrative Justice Act, the Moroccan Ruler, the Kuwaiti Law and the Egyptian Code of Procedure. Main results: 1- Adoption of the Algerian legislator for the administrative urgency in the material freedoms gained legislative and jumped quality as procedural protection. 2- The legislator does not adopt the ""unless it violates public order"" clause in article 171 bis of the former Civil Procedure Code in the provision on administrative urgency for the protection of fundamental freedoms. Key Recommendations: 1- refer to the individual system. 2- not to confuse the judge of urgency and the judge of cancellation. 3- Continuation of reforms and separation of the Civil Procedure Code from the Code of Administrative Civil Procedure. 4- Cancellation of the suspension system. 5- Failure to link between the case of suspension and the case for the protection of fundamental freedoms. "
قانون إداري
Keywords: الدعوى ، الإدارية ،الاستعجالية ، الحريات الأساسية; Administrative, urgent, fundamental freedoms